The influence of cotton fabric haecting perineum (PHP) on the perineum haecting practicum competence of midwifery students of the Salsabila Serang High School Of Health Sciences - Octavia, Rina; Halimatusyadiah, Leni; Lustiani, Ika; Adista, Nuria Fitri; Prihantiningsih, Anggarani (Science Midwifery, 2024)
Pantum is a tool to support the teaching and learning process and has an important role in supporting teaching and learning activities (Annisa, 2021). Perineal Haecting to stop bleeding and reconnect and restore the function of the vaginal mucosa, connective tissue and muscles (Aritonang, 2021). Perineal Haecting is one of the competencies that midwifery students must have (Elvira, 2023). The availability of Perineum Haecting Pantum (PHP) which can be used repeatedly in practicums is an ideal teaching tool because it is practical and more economical (Utami, 2023). This research uses the quantitative Quasy Experiment method with a one group pretest – posttest design. The sampling technique for this research was total sampling of 62 respondents. The research time is April-May 2024. Research methods use the Shapiro-Wilk statistical test. Based on the results of statistical tests, p = 0.001. This means that there is a significant difference between the perineal suturing abilities of the model group and the non-model group.